Should all patients with psoriasis receive statins? Analysis according to different strategies, - Walter Masson; Martín Lobo; Graciela Molinero; Emiliano Rossi (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Different strategies have been proposed for the cardiovascular risk management of patients with psoriasis. Objective: To estimate the cardiovascular risk and evaluate two cardiovascular prevention strategies in patients with psoriasis, analyzing which proportion of patients would be candidates to receive statin therapy. Methods: A retrospective cohort was selected from a secondary database. All patients >18 years with psoriasis without cardiovascular disease or lipid-lowering treatment were included. The atherosclerotic cardiovascular disease calculator (2018 American College of Cardiology/American Heart Association guidelines) and the Systematic Coronary Risk Evaluation risk calculator (2016 European Society of Cardiology/European Society of Atherosclerosis guidelines) were calculated. The SCORE risk value was adjusted by a multiplication factor of 1.5. The recommendations for the indication of statins suggested by both guidelines were analyzed. Results: A total of 892 patients (mean age 59.9 ± 16.5 years, 54.5% women) were included. The median atherosclerotic cardiovascular disease calculator and Systematic Coronary Risk Evaluation values were 13.4% (IQR 6.1-27.0%) and 1.9% (IQR 0.4-5.2), respectively. According to the atherosclerotic cardiovascular disease calculator, 20.1%, 11.0%, 32.9%, and 36.4% of the population was classified at low, borderline, moderate, or high risk. Applying the Systematic Coronary Risk Evaluation, 26.5%, 42.9%, 20.8%, and 9.8% of patients were stratified as having low, moderate, high, or very high risk, respectively. The proportion of subjects with statin indication was similar using both strategies: 60.1% and 60.9% for the 2018 American College of Cardiology/American Heart Association and 2016 European Society of Cardiology/European Society of Atherosclerosis guidelines, respectively. Study limitations: This was a secondary database study. Data on the severity of psoriasis and pharmacological treatments were not included in the analysis. Conclusion: This population with psoriasis was mostly classified at moderate-high risk and the statin therapy indication was similar when applying the two strategies evaluated.